GLOBAL TRENDS AND MODERN PROJECTS OF SOCIAL AND POLITICAL EVOLUTION - Liubashits, Valentin; Mamychev, Alexey; Plotnikov, Andrey; Shestopal, Sergey; Kachurova, Svetlana (Revista Inclusiones, 2021)
This article deals with the analysis of the modern approaches to the evolution of the concepts of the state and state power in a globalizing world. The approaches of representatives of various directions of political and legal thought are studied. The authors focus on the challenges to the traditional understanding of state sovereignty, on the transformation of state sovereignty, consider the differing points of view of realists and institutionalists on the need to revise the concept of sovereignty in the global world. They consider the role of international government organizations and other transnational regulators in regulating interstate relations, their influence on the transformation of the role of the states and state power in global processes. The authors prove that the adaptive potential of the state is aimed at reducing its role in the life of modern global society.